Tecnologia do bem estar: inovação organizacional e empreendedora - Santos, Millane Barbosa dos (2018)
The theme of spirituality grows significantly in organizations, associated with physical, mental and emotional aspects, presenting itself in organizations that seek ways to achieve excellence, not only in productivity, but in social responsibility and employee satisfaction. The aim of this paperis realize the tecnilogical prospect about the spirituality in the invention soft he main world markets, correlation its importance in the productive environmentsofindustry, science and technology. Search esweremade in the ORBIT system. The results aim to assist in the development of a social technology that use spiritual intelligence in Brazilian companies, serving a large part of the population. A total of 1036 documents were collected in the areas: computer technology, medical technology and games industries. It is concluded that theim plantation of spirituality in the tecnological and business areas presentes a high potential for expansion.